ANXIETY IN THE NARRATIVES OF THE DISPLACED BY THE WAR POPULATION - Sumbadze , Nana; Mitchenek , Beth; Regulska , Joanna; Kitiashvili, Ani; Pirtskalava, Ekaterine; Makharadze , Tamar; Maisuradze , Maia (Georgian Psychological Journal, 2022)
1908 August war was short but claimed many lives. Thousands have been displaced due to combat and bombing. Separation from the native places had a long lasting and severe effect on the well-being of popula- tion. Qualitative study was carried out to describe and measure the emotional reaction to war and displacement. Analysis of 5 minutes length narratives of the displaced population registered after 10 and 15 months from displacement by Gottshalk-Gleser method revealed high level of six types of anxiety measured by scales. The comparison of anxiety scores over time points at the persistence of negative emotional state induced by the war and at the importance of displacement, reﬂected both in number of references to displacement and separation anxiety scale scores.